Characterization of subgroups of heart failure patients with preserved ejection fraction with possible implications for prognosis and treatment response. (6th August 2015) - Kao, David P.; Lewsey, James D.; Anand, Inder S.; Massie, Barry M.; Zile, Michael R.; Carson, Peter E.; McKelvie, Robert S.; Komajda, Michel; McMurray, John JV; Lindenfeld, JoAnn
<x xml:space="preserve">Abstract</x> Background Patients with heart failure and preserved ejection fraction (HFpEF) have a poor prognosis, and no therapies have been proven to improve outcomes. It has been proposed that heart failure, including HFpEF, represents overlapping syndromes that may have different prognoses. We present an exploratory study of patients enrolled in the Irbesartan in Heart Failure with Preserved Ejection Fraction Study (I‐PRESERVE) using latent class analysis (LCA) with validation using the Candesartan in Heart failure: Assessment of Reduction in Mortality and morbidity (CHARM)‐Preserved study to identify HFpEF subgroups. Methods and results In total, 4113 HFpEF patients randomized to irbesartan or placebo were characterized according to 11 clinical features. The HFpEF subgroups were identified using LCA. Event‐free survival and effect of irbesartan on the composite of all‐cause mortality and cardiovascular hospitalization were determined for each subgroup. Subgroup definitions were applied to 3203 patients enrolled in CHARM‐Preserved to validate observations regarding prognosis and treatment response. Six subgroups were identified with significant differences in event‐free survival (P < 0.001). Clinical profiles and prognoses of the six subgroups were similar in CHARM‐Preserved. The two subgroups with the worst event‐free survival in both studies were characterized by a high prevalence of obesity, hyperlipidaemia, diabetes mellitus, anaemia, and renal insufficiency (Subgroup C) and by female predominance, advanced age, lower body mass index, and high rates of atrial fibrillation, valvular disease, renal insufficiency, and anaemia (Subgroup F). Conclusion Using a data‐driven approach, we identified HFpEF subgroups with significantly different prognoses. Further development of this approach for characterizing HFpEF subgroups is warranted.